2008
DOI: 10.1128/mcb.01536-07
|View full text |Cite
|
Sign up to set email alerts
|

p27kip1 Deficiency Impairs G2/M Arrest in Response to DNA Damage, Leading to an Increase in Genetic Instability

Abstract: p27kip1 is a cyclin-dependent kinase inhibitor and a tumor suppressor. In some tumors, p27 suppresses tumor growth by inhibition of cell proliferation. However, this is not universally observed, implying additional mechanisms of tumor suppression by p27. p27-deficient mice are particularly susceptibility to genotoxininduced tumors, suggesting a role for p27 in the DNA damage response. To test this hypothesis, we measured genotoxin-induced mutations and chromosome damage in p27-deficient mice. Both p27 ؉/؊ and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
45
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 41 publications
(35 reference statements)
5
45
1
Order By: Relevance
“…The pocket protein p107, along with p21 Waf1/Cip1 and p27 Kip1 , can restrain CDK2/CDK1-induced genomic instability during cell cycle exit, 29,36 and overexpression of cyclin E1-CDK2 can prevent nuclear translocation of repressor complexes containing p107 and p130. 37 Here we found that cyclin E1 overexpression also coincided with increased expression of p107, likely leading to negative feedback on cyclin E1-CDK2 activity.…”
Section: Resultsmentioning
confidence: 99%
“…The pocket protein p107, along with p21 Waf1/Cip1 and p27 Kip1 , can restrain CDK2/CDK1-induced genomic instability during cell cycle exit, 29,36 and overexpression of cyclin E1-CDK2 can prevent nuclear translocation of repressor complexes containing p107 and p130. 37 Here we found that cyclin E1 overexpression also coincided with increased expression of p107, likely leading to negative feedback on cyclin E1-CDK2 activity.…”
Section: Resultsmentioning
confidence: 99%
“…The pathways that were specifically enriched in adenomas in our analysis are known to be activated in colorectal carcinogenesis (causal, resulting or compensatory) such as the Wnt pathway (Midgley and Kerr, 1999), cell cycle routes (Hao et al, 1998), DNA base metabolism, transcription, ATM (Kwong et al, 2008;Paulson et al, 2008), ARF, p27 (Payne et al, 2008) and p53 (Einspahr et al, 2006) signaling routes. In addition, we found novel pathways unique to adenomas, among which are the Rb pathway, the Src pathway, folate biosynthesis and the PTC1 pathway.…”
Section: Discussionmentioning
confidence: 99%
“…These phenotypes are completely rescued in double Skp2 -/-p27 -/-mice, indicating that the accumulation of p27 in S, G 2 , and M phases in Skp2 -/-cells is responsible for a failure to progress to mitosis, resulting in polyploidy (20,21). Recently, several groups reported that ionizing radiation or DNAdamaging drugs could induce p27 expression to trigger an arrest in G 2 /M and that in the absence of p27, cells failed to undergo cell cycle arrest (22)(23)(24). Moreover, the loss of p27 was associated with increased chromosomal instability in response to DNA damage, as cells could proceed through mitosis with unrepaired DNA (22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several groups reported that ionizing radiation or DNAdamaging drugs could induce p27 expression to trigger an arrest in G 2 /M and that in the absence of p27, cells failed to undergo cell cycle arrest (22)(23)(24). Moreover, the loss of p27 was associated with increased chromosomal instability in response to DNA damage, as cells could proceed through mitosis with unrepaired DNA (22)(23)(24). In addition, p27 deficiency impeded Rad51-mediated DNA repair due to increased CDK1-mediated phosphorylation of BRCA2, which inhibits the BRCA2-Rad51 interaction and Rad51-mediated repair (22).…”
Section: Introductionmentioning
confidence: 99%